Nonchemical Weed Control for Home Landscapes and Gardens - Andrew MacRae; Marina D'Abreau (EDIS)
HS1170, a 3-page fact sheet by Andrew MacRae and Marina D’Abreau, lists some of the most common options for nonchemical weed control and descriptions of their pros and cons. Published by the UF Department of Horticultural Sciences, April 2010.